Perspective Al-Qur’an and Biology in Human Creation - Agustina, Fitri Dwi; Huda, M. Nurul (Journal Intellectual Sufism Research (JISR), 2020)
Abstract. Allah has ordered humans to pay attention to human creation, but the lack of human knowledge and understanding of the correlation of the Qur'an and Biology related to the process of human creation is one of the factors causing a person's lack of faith. This study aims to determine the creation of humans based on the Qur'an that has links with Biological Sciences. This research is library research whose information is obtained through the Qur'an, scientific articles, and biology books. The results of this study are the creation of humans based on the perspective of biology is that God created humans from the fusion of sperm cells and ovum cells. Sperm and ovum cells are part of the human body which are the same components of the human body as components of the soil that have been processed by plants through photosynthesis. Humans were created by God from the fusion of sperm cells from the testes and ovum cells from the ovaries, where the development of the two reproductive organs grows between the sulbi bone (backbone) and breast bone. And humans will be resurrected by God through human bones that are still left in the soil, namely the tailbone.